Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT